Pengungkapan Sustainability Reporting, Intellectual Capital, dan Nilai Perusahaan - Dewi, Putu Purnama; Dewi, Kadek Ayu Kreistya (E-Jurnal Akuntansi, 2022)
The study aims to determine the effect of sustainability reporting and intellectual capital disclosures on the value of mining companies listed on the Indonesia Stock Exchange in 2016-2020. This research used a purposive sampling technique in taking the sample using several relevant criteria. Obtained 35 observations as a research sample. The analysis technique used is multiple linear regression. The results of the study explain that the variable disclosure of sustainability reporting and intellectual capital has a positive and significant effect on firm value. Keywords: Disclosure of  Sustainability Reporting; Intellectual Capital; Firm Value.